Unsuccessful Developmental Experiences of People with ID and ASD as Risk Factors for Disorders in Psychosexual Functioning - Parchomiuk, Monika (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The article presents an analysis of the general characteristics of negative psychosocial experiences and their possible impact on the psychosexual sphere of children and adolescents with intellectual disabilities and autism spectrum disorders. Seeking such factors, the focus was on the family environment. Particular attention was paid to parental attitudes towards the child with indicated developmental disabilities and the child's sexuality. The tasks essential for the development of sexuality during childhood and adolescence were described. Possible problems and difficulties that may arise in this sphere in persons with developmental disabilities in the context of negative experiences were analyzed. General guidelines important for supporting parents were outlined, which are important from the perspective of limiting the adverse psychosocial experiences of children.